Shallow Torpor Expression in Free-Ranging Common Hamsters With and Without Food Supplements - Siutz, Carina; Ammann, Viktoria; Millesi, Eva (Frontiers in Ecology and Evolution, 2018)
Energy expenditure during winter can be reduced by expressing torpor, which is characterized by decreased metabolic rate and body temperature. In addition to deep, multiday torpor bouts alternating with short arousal episodes during the hibernation period, common hamsters can also enter shallow torpor bouts (STBs), lasting for less than 24 h at a minimum body temperature between 30-20 °C. Food supplements provided shortly before winter have been shown to shorten hibernation in males, but did not affect hibernation duration in females. In the presented study, we analyzed the expression of STBs and compared supplemented to unsupplemented common hamsters. Body temperature during winter was recorded using subcutaneously implanted data loggers (iButtons). The results revealed that supplemented males showed more STBs and thus spent more time in shallow torpor than unsupplemented individuals. The duration of STBs, however, was shorter in supplemented males and both mean and minimum body temperature were significantly higher compared to unsupplemented males. In females, shallow torpor expression did not differ between individuals with and without food supplements. STBs were mainly expressed before the onset of the first deep, multiday torpor bout, but the number of STBs was not related to that of deep torpor bouts. These results indicate that in males, shallow torpor combined with feeding on food stores could be the more appropriate overwintering strategy when sufficient external energy reserves are available. Females generally cache more food than males and are therefore assumed to be less affected by the additional food stores. These results underline the flexibility of the species in the use of heterothermy and could enable adequate and rapid responses to changes in food availability.